Trend Analysis of the Costing of Denim Wash: A Study on Bangladeshi Washing Industries - Nazrima Sultana; Md. Arif Iqbal; Md. Abdus Salam (European Scientific Journal, ESJ, 2019)
Denim industry is one of the largest in the global market due to its exotic fashion trend. Bangladesh is the largest exporter of denim products over the European market and just after China in worldwide production. Fashion sense in denim fabric is drastically increasing due to the introduction of multiple washing methods. It is a type of fabric finishing treated in a different way for the change of appearance. This paper focuses on the denim washing cost trend within the year 2010 to 2018, and it aims to find out various consequences to analyze the market status of denim washing. The study uses the primary data collected from ten leading denim washing factories in Bangladesh. The study shows that, around 2010, the trend of dry washing processes was not so familiar. Hence, around 2015, there was an extensive practice executed which dominates the conventional wet washing technologies. On the contrary, process like sandblasting got banned from around 2013 because of its harmful effects on workers and users. Besides, various expensive wet washing technologies like acid wash, stone enzyme wash, towel wash, brightener treatment, optical wash, etc. has been incorporated to provide quality washing effects. This paper shows the costing trend of different wash technologies. This is because the majority of the dry and wet wash technologies became more expensive with time gradually due to the increase in labor cost, utility costs, chemical, and process costs. Furthermore, it also shows that some new technologies, like laser technology, which provided effective cost with reasonable quality through the initial investments, are high. The paper gives a prediction for the upcoming trend of denim washing as well as the cost of the technologies.